STRATEGI PUBLIK RELATIONS DALAM MEMBANGUN CITRA PERUSAHAAN (Studi Deskriptif Membangun Hubungan Baik Dengan Media Dalam Upaya Meningkatkan Citra Perusahaan) - Siti Khadijah (Fakultas Komunikasi, Sastra, dan Bahasa, 2012)
Globalization era characterized by rapid development of technology allows public to communicate easily. A company should be able to follow developments and the market demands because the movement of information and communication, internal or external knowledge and public awareness are increasing. Industrial competition requires everything to be communicated transparently. The problem may simply arise unexpectedly. Small problems can become big if they are not taken seriously. These demands make the need of Public Relations firm in implementing the communication strategy of information to the public. Public Relations emerge as helper figure in crisis and are responsible for the development of company positive image. Positive image is not formed simply, but it takes appropriate communication strategies.Public Relations strategy is not enough done by implementing confidence to the public itself. Positive image that is built needs to be maintained and cared for, since it is closely related to the company's reputation. Once public reliance faded as a negative reputation, it will be difficult to restore the trust back.Reputation that has been done needs to be informed by the Public Relations through the media. Company media relations can enhance corporate publicity before the stakeholders. Installing confidence and building a positive reputation are ways to obtain a positive image. The success of Public Relations in getting publicity can be obtained from a harmonious relationship with the media.